Preparation method of ganoderan nano-selenium particles

By preparing Ganoderma lucidum polysaccharide nano-selenium particles, combining the advantages of Ganoderma lucidum polysaccharide and nano-selenium, the problems of low bioavailability and high toxicity are solved, achieving a highly efficient and safe nutritional supplement effect, which is suitable for functional foods and health products.

CN121337012APending Publication Date: 2026-01-16HUNAN DEBANG BIOLOGICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511510598.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing Ganoderma lucidum polysaccharides and inorganic selenium supplements suffer from low bioavailability, high toxicity, or high prices, making it difficult to achieve efficient and safe nutritional supplementation.

Method used

A method combining Ganoderma lucidum polysaccharides with nano-selenium particles was adopted. Zero-valent selenium was generated through a redox reaction and coated in Ganoderma lucidum polysaccharide matrix to form stable nano-selenium colloids. Amorphous nano-selenium particles were prepared by utilizing the steric hindrance of Ganoderma lucidum polysaccharides and the synergistic effect of surfactants.

Benefits of technology

The process achieves functional synergy between Ganoderma lucidum polysaccharides and nano-selenium, improving bioavailability and reducing toxicity. The preparation process is environmentally friendly and efficient, and the product is suitable for functional foods and health products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121337012A_ABST
    Figure CN121337012A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of ganoderan nano-selenium particles, and belongs to the field of nanotechnology and functional food. The method comprises the following steps: firstly, dissolving ganoderan, sodium selenite and a surfactant I in water to form a first dispersion liquid; adding ascorbic acid, and reacting at 20-60 DEG C for 1-2 hours to obtain a second red dispersion liquid; then adding a carrier and a surfactant II, and continuously stirring for 1-2 hours to obtain a third dispersion liquid with a Tyndall effect; and finally, carrying out pressure spray drying granulation to obtain the light red to dark red amorphous ganoderma lucidum polysaccharide nano-selenium particles with the Z-Aveage particle size of 100-1000 nm. The nano-selenium particles prepared by the invention have the advantages of small particle size, high bioavailability, low toxicity, good fluidity and the like, and are suitable for functional foods or health-care products for resisting oxidation, regulating immunity, resisting aging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of nanotechnology, in particular to a preparation method of ganoderma lucidum polysaccharide nano selenium particles. BACKGROUND

[0002] Ganoderma lucidum polysaccharide is an active ingredient extracted from ganoderma spore powder or ganoderma, which is a glucan with a three-stranded single sugar chain and a helical three-dimensional structure. Its three-dimensional structure is similar to deoxyribonucleic acid (DNA) and ribonucleic acid (RNA), and it is a macromolecular compound with a molecular weight distribution of several thousand to several hundred thousand daltons. Traditional ganoderma lucidum polysaccharide is mainly extracted from artificially cultivated or wild ganoderma fruiting bodies. Modern large-scale production relies on fermentation technology to separate and extract from ganoderma mycelium. Ganoderma lucidum polysaccharide can activate immune cells such as macrophages and T lymphocytes, promote the secretion of cytokines (such as interferon and interleukin), and enhance the body's ability to recognize and remove pathogens and abnormal cells. It may have certain auxiliary effects on people with low immunity or postoperative recovery. Studies have shown that it can inhibit tumor growth by inducing cancer cell apoptosis and inhibiting tumor angiogenesis, but it should be noted that it cannot replace regular treatment methods such as chemotherapy and should only be used as an auxiliary regulator. By removing free radicals, increasing superoxide dismutase (SOD) activity, and reducing oxidative stress damage, it may have an improvement effect on skin aging, chronic inflammation, and other health problems related to oxidation. It promotes liver cell regeneration and reduces liver damage caused by alcohol, drugs, and other factors. Animal experiments have shown that it can reduce the degree of liver fibrosis, but the specific mechanism still needs more clinical verification.

[0003] Selenium is an essential trace element for animals and plants, mainly involved in physiological processes such as antioxidant, immune regulation, and thyroid hormone metabolism. Common selenium supplements include inorganic selenium (sodium selenite, sodium selenate) and organic selenium (yeast selenium, selenomethionine), but inorganic selenium is highly toxic and has low bioavailability; organic selenium is less toxic but expensive and difficult to promote.

[0004] Nanomaterials have great application potential in the fields of optics, catalysis, and medicine due to their unique surface effects, small size effects, and quantum effects. In the field of nutrition and functional food, the introduction of nanotechnology provides a new solution for efficient delivery and absorption of trace elements.

[0005] Nanoseleium is one of the research hotspots in recent years. Nanoseleium has the same low cost as inorganic selenium and the same high bioavailability and low toxicity as organic selenium, making it a new type of selenium nutritional supplement with low cost, high bioavailability, and low toxicity. SUMMARY

[0006] The purpose of this invention is to provide a functional nano-selenium nutritional supplement with excellent antioxidant, immune-regulating, and anti-aging properties. It combines the advantages of both Ganoderma lucidum polysaccharides and nano-selenium, while achieving high bioavailability and low toxicity of selenium. Unless otherwise specified, "parts" in this document refer to parts by weight.

[0007] The technical solution adopted by this invention to solve its technical problem is as follows: A method for preparing Ganoderma lucidum polysaccharide selenium nanoparticles includes the following steps: In a 2L glass reactor, 50-150 parts of Ganoderma lucidum polysaccharide, 10-15 parts of sodium selenite, and 1-10 parts of surfactant I are dissolved in 500-1200 parts of water at a rotation speed of 80-200 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium. Then, 20-50 parts of ascorbic acid are added, and the mixture is stirred at 20-60℃ for 1-2 hours to obtain a red second dispersion. While stirring, 50-350 parts of carrier and 1-5 parts of surfactant II are added, and the stirring speed is adjusted to 200-600 r / min. Stirring is continued for 1-2 hours to obtain a third dispersion of Ganoderma lucidum polysaccharide selenium nanoparticles exhibiting the Tyndall effect. Finally, the third dispersion is subjected to pressure spray drying to granulate, obtaining light red to dark red amorphous Ganoderma lucidum polysaccharide selenium nanoparticles with a Z-Average particle size of 100-1000 nm.

[0008] The first dispersion has a solid content of 2-20% and is a light brown to reddish-brown transparent solution.

[0009] The Ganoderma lucidum polysaccharide is obtained by separating and extracting from Ganoderma lucidum mycelium using fermentation technology, and its purity is not less than 98%.

[0010] The sodium selenite and ascorbic acid mentioned herein have a purity of not less than 98%.

[0011] The surfactant I is any one or a combination of several of PEG4000, sodium dodecyl sulfate, Span 60, and Span 80, and the purity of PEG4000, sodium dodecyl sulfate, Span 60, and Span 80 is not less than 98%.

[0012] Preferably, the surfactant I is sodium dodecyl sulfate with a purity of 99%.

[0013] The stirring speed for preparing the first dispersion is 80-200 r / min.

[0014] The second dispersion has a solid content of 2-30% and is a dark red solution.

[0015] The mass ratio of sodium selenite to ascorbic acid is 1:(1.5-5).

[0016] Preferably, the mass ratio of sodium selenite to ascorbic acid is 1:(2-3).

[0017] The reaction temperature is 20-60℃.

[0018] Preferably, the reaction temperature is 30-40℃.

[0019] The reaction time is 1-2 hours.

[0020] Preferably, the reaction time is 1.5 hours.

[0021] The third dispersion has a solid content of 10-50% and is a red colloid exhibiting the Tyndall effect.

[0022] The carrier is any one or a combination of several of glycine, zinc sulfate, manganese sulfate, copper sulfate, ferrous sulfate, and magnesium sulfate, and the purity of glycine, zinc sulfate, manganese sulfate, copper sulfate, ferrous sulfate, and magnesium sulfate is not less than 95%.

[0023] Preferably, the carrier is a combination of glycine with a purity of 98% and magnesium sulfate with a purity of 98%, in a mass ratio of 10:(1-2).

[0024] The surfactant II is any one or a combination of several of sodium carboxymethyl cellulose, gelatin, xanthan gum, and gum arabic, and the effective ingredient content of sodium carboxymethyl cellulose, gelatin, xanthan gum, and gum arabic is not less than 90%.

[0025] Preferably, the surfactant II is sodium carboxymethyl cellulose, and its effective ingredient content is 99%.

[0026] The stirring speed for preparing the third dispersion is 200-600 r / min.

[0027] Preferably, the stirring speed is 400-600 r / min.

[0028] The pressure spray drying granulation process has an inlet air temperature of 160-220℃ and an outlet air temperature of 100-150℃.

[0029] Preferably, the inlet air temperature is 180-200℃ and the outlet air temperature is 130-140℃.

[0030] The pressure spray drying granulation process uses an atomizer pressure of 2-20 MPa.

[0031] Preferably, the pressure of the atomizer is 5-15 MPa.

[0032] The pressure spray drying granulation process has a feed rate of 500-2000 mL / min.

[0033] Preferably, the feeding rate is 1000-1500 mL / min.

[0034] This invention provides a method for preparing Ganoderma lucidum polysaccharide nano-selenium particles. The basic principle includes the following steps: First, sodium selenite reacts with ascorbic acid in a redox reaction to generate zero-valent selenium. Subsequently, under the action of surfactant I, the in-situ generated selenium particles are rapidly coated or adsorbed into the Ganoderma lucidum polysaccharide matrix, forming a composite dispersion system with selenium as the dispersed phase and Ganoderma lucidum polysaccharide as the continuous phase. Finally, with the assistance of surfactant II, the above dispersion system and a carrier are subjected to high-speed stirring to obtain a light red to dark red amorphous nano-selenium colloidal dispersion. The color depth of the solution is related to the content of zero-valent selenium; the higher the selenium content, the darker the color. The reaction equation for the generation of selenium is as follows: It should be noted that ascorbic acid first transforms into enol-form dehydroascorbic acid during oxidation, and this intermediate has poor stability. Subsequently, through a keto rearrangement reaction, it forms the more stable keto-form dehydroascorbic acid. The transformation process is shown below: Ganoderma lucidum polysaccharides, as the continuous phase, play an important role in this nano-selenium particle system: (1) Matrix and stabilizing effect: The abundant hydroxyl and carboxyl functional groups on the Ganoderma lucidum polysaccharide molecular chain can effectively capture, anchor and encapsulate the selenium nanoparticles generated in situ through coordination bonds, hydrogen bonds and physical adsorption. The addition of surfactant I further promotes this encapsulation process, enabling elemental selenium to be uniformly dispersed at the nanoscale in the three-dimensional network structure formed by the polysaccharide, forming a stable composite structure of "selenium core-polysaccharide shell".

[0035] (2) Steric Stabilization: As a high-molecular-weight hydrophilic colloid, Ganoderma lucidum polysaccharide can form a huge hydration layer and construct a spatial network in solution. This structure generates a strong steric hindrance effect, which can effectively prevent the coated nano-selenium particles from approaching each other, aggregating and settling due to van der Waals forces, thereby ensuring that the colloidal dispersion has excellent kinetic stability.

[0036] (3) Synergistic modification and guidance: Under the synergistic effect of surfactant II, the continuous phase of Ganoderma lucidum polysaccharide and the carrier material can be more uniformly combined under high-speed stirring, and jointly guide the final formation of uniform and stable amorphous nano-selenium colloid.

[0037] The nano-selenium prepared in this way has excellent stability and biocompatibility, and endows it with dual biological activities of Ganoderma lucidum polysaccharide and selenium.

[0038] The carrier in this system mainly provides a dispersion matrix, adjusts the selenium content of the final product, and provides structural support, which helps to improve the stability of the nano-selenium colloidal solution and facilitates subsequent drying and molding.

[0039] The superior effects of the technical solution of the present invention are as follows: (i) The preparation method provided by the present invention has few steps and mild reaction conditions, and has good process repeatability and potential for large-scale production.

[0040] (ii) Continuous granulation is achieved by using pressure spray drying technology. The water vapor generated during the process is recycled after dust removal and condensation treatment, with no wastewater discharge, which meets the requirements of green environmental protection.

[0041] (iii) The resulting product consists of amorphous nanoparticles ranging from light red to dark red, with a controllable particle size distribution. The selenium content can be precisely controlled by adjusting the raw material ratio. The product particles have a regular shape and excellent flowability, facilitating subsequent processing and application.

[0042] (iv) The nano-selenium particles have the physiological activities of both Ganoderma lucidum polysaccharides and selenium, achieving synergistic effects, high bioavailability and good safety, and significantly lower toxicity than traditional selenium preparations. They are suitable for functional foods and health products. Attached Figure Description

[0043] Figure 1 : Scanning electron microscope (SEM) image of Ganoderma lucidum polysaccharide nano-selenium obtained in Example 1; Figure 2 XRD pattern of Ganoderma lucidum polysaccharide nano-selenium obtained in Example 3; Figure 3 Example 4: Z-Average particle size distribution of Ganoderma lucidum polysaccharide nano-selenium obtained; Figure 4 : Flowchart of the preparation process of this invention. Detailed Implementation

[0044] To achieve the preparation of the Ganoderma lucidum polysaccharide selenium nanoparticles described in this invention, a detailed description is provided below with reference to specific embodiments.

[0045] Analysis Appendix Figure 1 The SEM image of Ganoderma lucidum polysaccharide nano-selenium shows that the prepared particles exhibit a regular spherical morphology, a smooth and flat surface, good dispersion, and a relatively concentrated particle size distribution. No obvious agglomeration phenomenon was observed, indicating that this method can successfully prepare nanoscale particles with complete structure and uniform morphology.

[0046] Appendix Figure 2The XRD diffraction pattern showed that it did not have sharp crystalline diffraction peaks, but instead exhibited a broad diffuse diffraction pattern (bun peaks). This feature is consistent with the typical XRD pattern of amorphous substances, further confirming that the prepared selenium nanoparticles have an amorphous structure.

[0047] Appendix Figure 3 The Z-Average particle size distribution diagram of Ganoderma lucidum polysaccharide nano-selenium shown in the figure indicates that the particle size of the product is mainly concentrated in the range of 100 to 200 nm, and the particle size distribution range is relatively narrow. This further verifies that the preparation method of the present invention has good repeatability and reliability in controlling particle size and distribution.

[0048] Figure 4 This is a flowchart illustrating the preparation process of the present invention.

[0049] Example 1 In a 2L glass reactor, 68g of Ganoderma lucidum polysaccharide (99%), 12g of sodium selenite (99%), and 5g of sodium dodecyl sulfate (99%) were dissolved in 800g of water at 100 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 9.60%. Then, 30g of ascorbic acid (99%) was added, and the mixture was stirred at 30℃ for 1.5 hours to obtain a second red dispersion with a solid content of 12.57%. While stirring, 300g of glycine (98%), 30g of zinc sulfate (98%), and 3g of sodium carboxymethyl cellulose (95%) were added sequentially. The stirring speed was adjusted to 500 r / min, and stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 35.90%. Finally, the third dispersion was subjected to pressure spray drying granulation under the conditions of an inlet air temperature of 180℃, an outlet air temperature of 130℃, an atomizer pressure of 8 MPa, and a feed rate of 1000 mL / min to obtain light red Ganoderma lucidum polysaccharide selenium nanoparticles, the morphology of which is as follows: Figure 1 As shown, the nanoparticles are uniformly spherical. The yield was 400.9g, with a yield of 89.5%, and the selenium content was determined to be 1.19%.

[0050] Example 2 In a 2L glass reactor, 125g of Ganoderma lucidum polysaccharide (99%), 12g of sodium selenite (99%), and 5g of PEG4000 (98%) were dissolved in 650g of water at 120 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 17.93%. Then, 25g of ascorbic acid (99%) was added, and the mixture was stirred at 30℃ for 1.5 hours to obtain a second red dispersion with a solid content of 20.44%. While stirring, 240g of glycine (98%), 35g of manganese sulfate (98%), and 2g of xanthan gum (92%) were added sequentially. The stirring speed was adjusted to 400 r / min, and stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 40.58%. Finally, the third dispersion was subjected to pressure spray drying and granulation under the conditions of an inlet air temperature of 200℃, an outlet air temperature of 135℃, an atomizer pressure of 8 MPa, and a feed rate of 1000 mL / min to obtain light red Ganoderma lucidum polysaccharide nano-selenium particles, weighing 405.37 g, with a yield of 91.3% and a selenium content of 1.21%.

[0051] Example 3 In a 2L glass reactor, 50g of Ganoderma lucidum polysaccharide (99%), 15g of sodium selenite (99%), and 2g of Span 60 (98%) were dissolved in 1000g of water at 150 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 6.28%. Then, 35g of ascorbic acid (99%) was added, and the mixture was stirred at 35℃ for 1.5 hours to obtain a second red dispersion with a solid content of 9.26%. While stirring, 50g of glycine (98%), 10g of magnesium sulfate (96%), and 1g of gelatin (92%) were added sequentially. The stirring speed was adjusted to 600 r / min, and stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 14.02%. Finally, the third dispersion was subjected to pressure spray drying granulation under the following conditions: inlet air temperature of 190℃, outlet air temperature of 130℃, atomizer pressure of 10MPa, and feed rate of 1500 mL / min, to obtain dark red Ganoderma lucidum polysaccharide selenium nanoparticles, weighing 147.84 g, with a yield of 90.7% and a selenium content of 4.08%. The XRD diffraction pattern of the product is attached. Figure 2 .

[0052] Example 4 In a 2L glass reactor, 50g of Ganoderma lucidum polysaccharide (99%), 15g of sodium selenite (99%), and 2g of Span 60 (98%) were dissolved in 1000g of water at 180 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 6.28%. Then, 32g of ascorbic acid (99%) was added, and the mixture was stirred at 35℃ for 1.5 hours to obtain a second red dispersion with a solid content of 9.01%. While stirring, 120g of glycine (98%) and 2g of gelatin (95%) were added sequentially, and the stirring speed was adjusted to 600 r / min. Stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 18.10%. Finally, the third dispersion was subjected to pressure spray drying granulation under the following conditions: inlet air temperature of 210℃, outlet air temperature of 140℃, atomizer pressure of 10 MPa, and feed rate of 1500 mL / min, to obtain red Ganoderma lucidum polysaccharide nano-selenium particles, weighing 203.54 g, with a yield of 92.1% and a selenium content of 3.02%. The particle size distribution of the product is shown in the appendix. Figure 3 .

[0053] Example 5 In a 2L glass reactor, 100g of Ganoderma lucidum polysaccharide (99%), 14g of sodium selenite (99%), and 3g of sodium dodecyl sulfate (99%) were dissolved in 600g of water at 80 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 16.32%. Then, 30g of ascorbic acid (99%) was added, and the mixture was stirred at 40℃ for 1 hour to obtain a second red dispersion with a solid content of 19.68%. While stirring, 150g of glycine (98%), 15g of manganese sulfate (98%), and 2g of gum arabic (92%) were added, and the stirring speed was adjusted to 200 r / min. Stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 34.35%. Finally, the third dispersion was subjected to pressure spray drying and granulation under the conditions of an inlet air temperature of 220℃, an outlet air temperature of 140℃, an atomizer pressure of 15 MPa, and a feed rate of 1800 mL / min to obtain red Ganoderma lucidum polysaccharide nano-selenium particles, weighing 288.25 g, with a yield of 91.8% and a selenium content of 1.97%.

[0054] To further illustrate the advantages of the preparation method of Ganoderma lucidum polysaccharide nano-selenium particles provided by this invention, comparative experiments were conducted by changing raw materials, process conditions and parameters, in conjunction with existing technologies.

[0055] Comparative Example 1 (changing the feeding sequence of Example 3) In a 2L glass reactor, 50g of Ganoderma lucidum polysaccharide (99%), 15g of sodium selenite (99%), 2g of Span 60 (98%), 35g of ascorbic acid (99%), 50g of glycine (98%), 10g of magnesium sulfate (96%), and 1g of gelatin (92%) were dissolved in 1000g of water and reacted at 35℃ with a stirring speed of 600 r / min for 2 hours. During this process, the color of the reaction solution gradually changed from red to dark black, and precipitates were formed. Then, under pressure spray drying conditions of 190℃ inlet air temperature, 130℃ outlet air temperature, 10 MPa atomizer pressure, and 1500 mL / min feed rate, the product was obtained as dark black fine particles, weighing 137.9g, with a yield of 84.6%, and a selenium content of 4.03%.

[0056] Comparative Example 2 (Changing the temperature conditions of Example 4) In a 2L glass reactor, 50g of Ganoderma lucidum polysaccharide (99%), 15g of sodium selenite (99%), and 2g of Span 60 (98%) were first dissolved in 1000g of water at 180 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 6.28%. Then, 32g of ascorbic acid (99%) was added, and the mixture was stirred at 80℃ for 1.5 hours. The reaction solution started as red and then gradually turned black. While stirring, add 120g glycine (98%) and 2g gelatin (95%) in sequence, adjust the stirring speed to 600 r / min, and continue stirring for 1 hour. Finally, under the conditions of inlet air temperature of 210℃, outlet air temperature of 140℃, atomizer pressure of 10 MPa, and feed rate of 1500mL / min, perform pressure spray drying granulation to obtain black fine particles, weighing 182.33g, with a yield of 82.5% and a selenium content of 2.98%.

[0057] Comparative Example 3 (with modified pressure spray drying granulation conditions from Example 2) In a 2L glass reactor, 125g of Ganoderma lucidum polysaccharide (99%), 12g of sodium selenite (99%), and 5g of PEG4000 (98%) were dissolved in 650g of water at 100 r / min to form a first dispersion of Ganoderma lucidum polysaccharide selenium with a solid content of 17.93%. Then, 25g of ascorbic acid (99%) was added, and the mixture was stirred at 30℃ for 1.5 hours to obtain a second red dispersion with a solid content of 20.44%. While stirring, 240g of glycine (98%), 35g of manganese sulfate (98%), and 2g of xanthan gum (92%) were added sequentially. The stirring speed was adjusted to 400 r / min, and stirring was continued for 1 hour to obtain a third dispersion of Ganoderma lucidum polysaccharide nano-selenium colloid with a solid content of 40.58%. Finally, the third dispersion was subjected to pressure spray drying and granulation under the conditions of an inlet air temperature of 150°C, an outlet air temperature of 85°C, an atomizer pressure of 1 MPa, and a feed rate of 1000 mL / min. The resulting product was a light red powder that adhered to the wall and had poor flowability. It weighed 376.96 g, with a yield of 84.9%, and the selenium content was found to be 1.15%.

[0058] The product detection results of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below. Yield = actual yield / feed amount * 100%, where feed amount does not include solvent water. Selenium content was determined by ICP-MS (model: NexION 1000G) according to Method I of GB 5009.268-2016, and particle size was determined by laser particle size analyzer (model: Mastersizer 2000), with a detection range of 0.02-2000 μm.

[0059] Table 1. Detection results of products from the examples and comparative examples. The feasibility and superiority of the preparation method were verified through multiple embodiments and comparative examples. The Ganoderma lucidum polysaccharide selenium nanoparticles prepared in Examples 1–5 all exhibited light red to dark red colors, with particle sizes ranging from 179 to 634 nm. The yields were all above 89%, and the selenium content was controllable between 1.19% and 4.08%. Furthermore, the products showed good flowability, indicating that the method has good repeatability and stability.

[0060] Comparative Examples 1–3 show that changing the feeding sequence, increasing the reaction temperature, or adjusting the spray drying parameters will lead to abnormal product color, increased particle size, decreased yield, or poor flowability, further confirming the necessity and rationality of the process conditions described in this invention.

[0061] In summary, the preparation method provided by this invention is simple, mild, environmentally friendly and efficient. The resulting nano-selenium particles have both the physiological activities of Ganoderma lucidum polysaccharides and selenium, and have high bioavailability, low toxicity and good processing performance, making them suitable for the field of functional foods and health products.

[0062] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, combinations, modifications and simplifications made without departing from the principles of the present invention should be considered within the protection scope of the present invention.

Claims

1. A method for preparing Ganoderma lucidum polysaccharide selenium nanoparticles, characterized in that, Includes the following steps: (1) Dissolve Ganoderma lucidum polysaccharide, sodium selenite and surfactant I in water to form a first dispersion; (2) Add ascorbic acid to the first dispersion and stir at 20-60°C for 1-2 hours to obtain a red second dispersion; (3) Add the carrier and surfactant II to the second dispersion and continue stirring at a speed of 200-600 r / min for 1-2 hours to form a third dispersion with Tyndall effect; (4) The third dispersion is spray-dried and granulated to obtain Ganoderma lucidum polysaccharide nano-selenium particles; The spray drying process includes an inlet air temperature of 160–220°C, an outlet air temperature of 100–150°C, an atomizer pressure of 2–20 MPa, and a feed rate of 500–2000 mL / min.

2. The preparation method according to claim 1, characterized in that, In step (1), the components are as follows by mass: 50-150 parts of Ganoderma lucidum polysaccharide, 10-15 parts of sodium selenite, 1-10 parts of surfactant I, and 500-1200 parts of water; the solid content of the first dispersion is 2%-20%.

3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the amount of ascorbic acid added is 20 to 50 parts by mass; the mass ratio of sodium selenite to ascorbic acid is 1:(1.5 to 5).

4. The preparation method according to claim 3, characterized in that, In step (2), the mass ratio of sodium selenite to ascorbic acid is 1:(2-3); the reaction temperature is 30-40℃; and the reaction time is 1.5 hours.

5. The preparation method according to claim 1, characterized in that, Surfactant I is selected from one or more of polyethylene glycol 4000, sodium dodecyl sulfate, Span 60, and Span 80; surfactant II is selected from one or more of sodium carboxymethyl cellulose, gelatin, xanthan gum, and gum arabic.

6. The preparation method according to claim 1, characterized in that, In step (3), the amount of carrier added is 50 to 350 parts by mass, and the carrier is selected from one or more of glycine, zinc sulfate, manganese sulfate, copper sulfate, ferrous sulfate, and magnesium sulfate.

7. The preparation method according to claim 1, characterized in that, In step (4), the inlet air temperature of the spray dryer is 180-200℃ and the outlet air temperature is 130-140℃.

8. The preparation method according to claim 1, characterized in that, In step (4), the pressure of the atomizer is 5 to 15 MPa.

9. The preparation method according to claim 1, characterized in that, In step (4), the feeding rate is 1000-1500 mL / min.

10. A type of Ganoderma lucidum polysaccharide selenium nanoparticle prepared by the method according to any one of claims 1 to 9, characterized in that, The particles are amorphous nanoparticles ranging from light red to dark red, with a Z-Average particle size of 100–1000 nm and a polydispersity index (PDI) ≤0.3; the particles are used in the preparation of functional foods, health foods, or pharmaceuticals for antioxidant, immunomodulatory, or anti-aging purposes.